AN ESP NEEDS ANALYSIS FOR TRAVEL VLOGGERS: EVIDENCE FROM VLOG DISCOURSE (INFERENCE: Journal of English Language Teaching, 2026)
The travel vlogger profession demands specific English language competencies for effective tourism promotion. This study aims to conduct a Needs Analysis for EFL vloggers through discourse analysis. Using six samples of Indonesian destination vlogs from YouTube, this study applies an analysis of rhetorical moves and linguistic features. The findings indicate a gap between the target situation (TSA) and the present situation (PSA); vloggers tend to only use basic narrative structures and underutilize directive expressions to provide recommendations that build rapport with viewers. Therefore, this study suggests a curriculum focused on mastering narrative scripts and recommendation phrases. This implementation is expected to bridge the skills gap and increase audience engagement in digital tourism promotion.
Keywords: travel vlogs; ESP; Needs Analysis; storytelling; Indonesia